Highlights of the São Paulo ISEV workshop on extracellular vesicles in cross-kingdom communication. Issue 1 (1st December 2017) - Soares, Rodrigo P.; Xander, Patrícia; Costa, Adriana Oliveira; Marcilla, Antonio; Menezes-Neto, Armando; Del Portillo, Hernando; Witwer, Kenneth; Wauben, Marca; Nolte-`T Hoen, Esther; Olivier, Martin; Criado, Miriã Ferreira; da Silva, Luis Lamberti P.; et al.
ABSTRACT: In the past years, extracellular vesicles (EVs) have become an important field of research since EVs have been found to play a central role in biological processes. In pathogens, EVs are involved in several events during the host–pathogen interaction, including invasion, immunomodulation, and pathology as well as parasite–parasite communication. In this report, we summarised the role of EVs in infections caused by viruses, bacteria, fungi, protozoa, and helminths based on the talks and discussions carried out during the International Society for Extracellular Vesicles (ISEV) workshop held in São Paulo (November, 2016), Brazil, entitled Cross-organism Communication by Extracellular Vesicles: Hosts, Microbes and Parasites.